Preservation bias obscures gradual Ordovician reef evolution - Juwan Jeon; Qi-Jian Li; Jeong-Hyun Lee (Proceedings of the National Academy of Sciences, 2025)
The fossil record often creates an illusion of sudden evolutionary bursts, which may reflect preservation biases rather than actual biological events. The Great Ordovician Biodiversification Event (GOBE) appears to mark the abrupt rise of diverse reef-building metazoans during the late Darriwilian (~460 Ma), seemingly contradicting gradual evolutionary models. Here, we demonstrate this apparent burst is largely an artifact of a global sea-level fall (~475 to 460 Ma) that produced widespread unconformities. Integrated stratigraphic and fossil occurrence data reveal early reef-builders likely appeared earlier than the late Middle Ordovician, but their record was erased by sea-level-driven erosion. During the peak of this sea-level fall (Dapingian Stage, 471 to 469 Ma), both carbonate deposition and fossil occurrences were minimal, with significant correlation between carbonate preservation and reef-builder occurrences. The subsequent transgression enabled these already-diversified organisms to recolonize shallow-water environments simultaneously across multiple regions, generating a misleading impression of sudden diversification. This “Sppil–Rongis effect” biased our understanding of the GOBE in reef ecosystems, illustrating how stratigraphic incompleteness can distort evolutionary patterns. Rather than a discrete evolutionary event, the GOBE reflects a continuous trajectory, interrupted and reshaped by sea-level fluctuations.